Real-world palbociclib dose modifications and clinical outcomes in patients with HR+/HER2− metastatic breast cancer: A Flatiron Health database analysis - Rachel M. Layman; Xianchen Liu; Benjamin Li; Lynn McRoy; Adam Brufsky (Breast)
Purpose: To examine the associations of palbociclib dose modifications with clinical outcomes of patients with HR+/HER2− metastatic breast cancer (MBC) treated with first-line (1L) palbociclib + aromatase inhibitor (AI) in routine practice. Methods: Using the Flatiron Health Analytic Database, we conducted a retrospective analysis of HR+/HER2− MBC patients who started 1L palbociclib + AI February 2015–March 2020. Kaplan−Meier analyses were used to estimate treatment duration, real-world progression-free survival (rwPFS), and overall survival (OS) by palbociclib dose adjustments (any change in palbociclib daily dose while on treatment) and dose reductions (starting dose <125 mg/day or dose reduced while on treatment). Cox proportional hazard regression models were performed to compute unadjusted/adjusted hazard ratios (HRs). Results: Of 1302 patients with documented starting dose, 524 (40.2 %) had palbociclib dose adjustments; 778 (59.8 %) had none. Median treatment duration was significantly longer in patients with dose adjustments versus those with none (27.4 vs 21.4 months; adjusted HR = 0.80 [95 % CI, 0.69–0.93]; P = 0.004). Patients with and without dose adjustments showed similar median rwPFS (20.5 vs 19.6 months; adjusted HR = 0.89 [95 % CI, 0.76–1.04]; P = 0.133). Median OS was significantly prolonged in patients with versus without dose adjustments (57.8 vs 51.4 months; adjusted HR = 0.73 [95 % CI, 0.59–0.89]; P = 0.002). Similar findings were observed in patients with and without dose reductions. Conclusions: In this real-world study, rwPFS in HR+/HER2− MBC patients was maintained irrespective of dose adjustments. However, dose adjustments were associated with extended treatment duration and OS. Clinical trial registration: NCT05361655 (ClinicalTrials.gov)